(untitled) (Research, Society and Development, 2022)
The species Iroxa chinensi popularly known as giant pin, is used in the preparation of hydroalcoholic extracts used as natural indicators of acidic and basic substances. This study aimed to obtain an acid-base indicator hydroalcoholic solution from the species Iroxa chinensi for qualitative testing (visualization of color in everyday acid and basic solutions) and qualitative test (determination of the percentage of acetic acid contente in vinegars) marketed in the city of Breves in the State of Pará). This study was carried out in several stages, namely: the preparation of the hydroalcoholic extratct from Iroxa chinensi and later the production of pH strips; tests using both the extract and the pH strip in prepared solutions and everyday products; and determination of acetic acid content in comercial vinegars. The results showed the efficiency of the hydroalcoholic extract of Iroxa chinensi as a natural acid-base indicator, as well as the pH tape proved to be a viable tool in the identification of acidic and basic substances. Therefore, there is a potential in the use of natural indicators to identify acidic and basic substances of everyday life, taking into account the easy obtainment of these resources, low cost and efficiency of the results obtained, thus being able to replace synthetic indicators, in addition to being a tool that can be easily produced and worked on in the classroom.